Complements or Substitutes? Examining the Relationship between Teamwork and Selection Intensity - Alberto Bayo-Moriones; Jose Enrique Galdon-Sanchez; Sara Martinez-de-Morentin (Institute of Labor Economics (IZA), 2024)
Teamwork has become widely embraced in recent decades; however, its adoption carries significant implications that require thorough understanding. In this paper, we study the relationship between teamwork and selection intensity. The use of teams may increase the value of investing in comprehensive selection, as it facilitates the identification of workers with complementary skills. However, teamwork may also substitute intensive selection if team members engage in mutual monitoring and peer reporting. Using data from a representative sample of Spanish manufacturing plants, we find a significant and negative association between selection intensity and teamwork that is aligned with the mutual monitoring hypothesis.
Keywords: M50; M51; M12; 330; teamwork; selection intensity; mutual monitoring; HRM complementarity